1987
DOI: 10.1017/s0031182000053944
|View full text |Cite
|
Sign up to set email alerts
|

The blocking of human antibody-dependent, eosinophil-mediated killing ofSchistosoma mansonischistosomula by monoclonal antibodies which cross-react with a polysaccharide-containing egg antigen

Abstract: SUMMARYThree IgM monoclonal antibodies, M22G11P, M7B7 and M22B3G, which reacted with the surfaceof Schistosoma mansonischistosomula in an indirect fluorescent antibody assay, were found to recognize a polysaccharide-containing egg antigen previously designated K3. The monoclonal antibodies and a monospecific rabbit anti-K3serum also recognized a crossreacting antigen in a crude cercarial antigen preparation. In an eosinophil-mediated schistosomulum killing assay, all three monoclonal antibodies significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…These authors observed that et al (1985). Further studies on Ig isotypes secreted around juvenile flukes are necessary to explore this antibody-blocking evasion mechanism, which has also been described in schistosomes (Capron et al, 1987;Dunne et al 1987). While F. hepatica seems able to evade ADCC mechanisms, which may be regulated by Th2 cytokines, further studies are needed to explore the role of the parasite in regulation of the immune response.…”
Section: Hepatic Lymph Nodementioning
confidence: 97%
“…These authors observed that et al (1985). Further studies on Ig isotypes secreted around juvenile flukes are necessary to explore this antibody-blocking evasion mechanism, which has also been described in schistosomes (Capron et al, 1987;Dunne et al 1987). While F. hepatica seems able to evade ADCC mechanisms, which may be regulated by Th2 cytokines, further studies are needed to explore the role of the parasite in regulation of the immune response.…”
Section: Hepatic Lymph Nodementioning
confidence: 97%
“…Initially, two different K3 ELISA assays were compared. The first involved the use of a mouse monoclonal IgM antibody (mAb), M22GllP, which blocks eosinophil killing of schistosomula [17], bound to ELISA plates in order to capture K3 from SEA. The second method employed the same IgM mAb, covalently linked to Sepharose beads, to immunoaffinity purify the K3 antigen from SEA.…”
Section: Antigensmentioning
confidence: 99%
“…Cultured schistosomular shed antigen (Shed.SA) was recovered from the supernatant fluid collected from an 18-h culture ELISA assays were also carried out using the polysaccharide egg antigen K3, which had been immunoaffinity purified from SEA using purified mouse IgM anti-K3 mAb, M22GllP [17] covalently linked to CNBr-activated Sepharose. This assay was compared with a second K3 ELISA assay in which the same mAb, which had been highly purified by gel filtration HPLC, was coated directly on microtiter plates overnight.…”
Section: Antigensmentioning
confidence: 99%
“…The diirerenl helminthiasis are among the most prevalent of chronic infections of humans, and numerous studies have demonstrated thai there is a process of constant reinfection in endemic areas [1,2], One of the most interesting features of the immtme response to these parasites is the produetion of IgE antibodies [3], and there exists considerable evidence that ihe IgE response may participate in the protection against helminthic infection [4][5][6][7]. For example, the allergic-type reactions mediated by the interaction beiween IgE and mast cells may be important accessory mechanisms in helminih expulsion [8].…”
Section: Introductionmentioning
confidence: 99%